Application of the Make a Match Type Cooperative Learning Model Assisted by Mind Mapping to Improve Student Science Learning Outcomes - Fathurrahmaniah, Fathurrahmaniah; Ewisahrani, Ewisahrani; Nursaban, Eva (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The aim of this research is to determine the effect of the make a match type cooperative learning model assisted by mind mapping in improving science learning outcomes for fourth grade students at SDN Tonda. In their learning, fourth grade students at SDN Tonda Dalamtaking science lessons tends to be passive as well bored in carrying out learning activities so that the learning outcomes obtained tend to be low compared to other subjects as evidenced by learning outcomes that are less than the KKM. This research is Classroom Action Research (PTK) with the research subjects being all fourth grade students at SDN Tonda who are divided into control classes and experimental classes. The control class was taught using the make a match type cooperative learning method, while the experimental class was taught using the make a match type cooperative learning model assisted by mind mapping to improve student learning outcomes. This research was conducted in two cycles, cycle I completeness of student learning outcomes 53,34% and cycle II increased to 93,33%. This proves that make a match type cooperative learning assisted by mind mapping is a learning method that can improve the learning outcomes of class IV students at SDN Tonda